IMPROVING INTEGRITY OF CLASSES, TEACHERS AND SCHOOLS: EMPIRICAL ANALYSES ON EDUCATION MARKET INDICATORS - Shakirova, Dilfuza; Rakhimova, Shirin; Babayeva, Komila; Karimov, Farkhod; Komilova, Ziroatkhon (International Journal of Psychosocial Rehabilitation, 2020)
In this paper work it is studied content of the education system and program which include integrated and result-oriented school teaching methodology. Methods and means of teaching integrated learning in primary school, integration and innovation in teaching subjects. Main objectives of the paper are finding out root cause of the integration study, interdisciplinary communication in the teaching process, integrated lessons in the primary education, integrated planning, the development of children's development, individual development of children and classes. Purpose of the current paper are defined teaching pedagogical strategy and find out the most relevant of teaching methods for primary education in case of diversity obtain prominent results among schools, teachers and classes in mathematical analyses. Outcomes of the article are integration ways of science cycles, as well as the plan of the primary educational plan, raising visibility of schools and students among others and the implement modern psychological, pedagogical and innovative target-oriented methods and hints, analysis of the experimental performance of the homework distributed.